Cardioband, a transcatheter surgical-like direct mitral valve annuloplasty system: early results of the feasibility trial - Maisano, Francesco; Taramasso, Maurizio; Nickenig, Georg; Hammerstingl, Christoph; Vahanian, Alec; Messika-Zeitoun, David; Baldus, Stephan; Huntgeburth, Michael; Alfieri, Ottavio; Colombo, Antonio; La Canna, Giovanni; Agricola, Eustachio; et al. (European heart journal, 2016)
Cardioband system is a direct annuloplasty adjustable device that is implanted in the beating heart on the posterior annulus under fluoroscopic and transoesophageal echocardiographic (TEE) guidance. We report the early (1 month) outcomes of the first-in-man pre-CE-mark feasibility and safety trial. The study enrolled high-risk adult individuals at five institutions in Europe with symptomatic secondary mitral regurgitation (MR) despite optimal medical therapy. The primary efficacy endpoints included the technical success rate of implantation, feasibility of the Cardioband adjustment (technical performance), and ability to reduce the annular septolateral dimension and MR grade at hospital discharge and at 30 days. The study group included 31 consecutively enrolled high-risk patients with moderate-to-severe or severe secondary MR with at least 1 month of follow-up (mean age 71.8 ± 6.9 years). All patients received the full implant of a Cardioband. Adjustment of the Cardioband resulted in a significant reduction in the septolateral dimension in all but two patients (septolateral dimension from 36.8 ± 4.8 to 29 ± 5.5 mm after the procedure, P < 0.01). Following Cardioband adjustment (29 of 31 patients) MR was none or trace in 6 (21%), mild in 21 (72%), and moderate in 2 (7%). No patient had severe MR after adjustment. Procedural mortality was zero and in-hospital mortality was 6.5% (2 of 31 patients, neither procedure- nor device-related). At 30 days, 22 of the 25 patients (88%) had MR ≤2+. This study demonstrates the feasibility and safety of percutaneous direct mitral annuloplasty with the Cardioband device in high-risk patients with MR.